Implementation of Physics Concepts in Energy Conversion-Based Electronic Devices as Physics Teaching Materials - Nurita Apridiana Lestari; Ridwan Rahman; Riza Pratami; Eka Putri Nata Sari; Dwikoranto (Studies in Philosophy of Science and Education, 2021)
This study aims to analyze the concepts of physics in electric scooters, solar panel street lights, and water heaters as physics teaching materials. The research method used in this research is a qualitative method with literature study. Data collection techniques in this study consisted of observation and documentation. Observation is done by observing directly and then documented. The data analysis technique used is to perform data reduction and then draw conclusions. The results obtained are the concepts related to scooters, solar panel street lights, and water heaters are the principles of energy conversion, direct electricity, and heat. In an electric scooter, energy conversion occurs from electrical energy into motion energy, a solar panel street light converts solar energy into electrical energy, and a water heater converts electrical energy into heat energy. That way, it can be an alternative teaching material in learning with concrete examples in the surrounding environment. So that it can make the learning process more meaningful.